Analysis of Transactional Leadership, Motivation and Career Development on Employee Performance at PT Erajaya Medan - Farhan Difa Ansari; Darmilisani Darmilisani (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
In today's highly competitive business world, the performance of employees is essential for reaching the goals of the organization. Initial observations at PT Erajaya Medan indicate gaps in the quality of work, supervision, motivation, and opportunities for career advancement, which implies that employees are not receiving sufficient support and growth prospects. These challenges underline the importance of examining key factors influencing performance, particularly leadership style, employee motivation, and career development programs. The objective of the current study was to understand how transactional leadership, motivation, and career development affect PT Erajaya Medan employees' performance. Given the limited scope of the population, a descriptive quantitative methodology was employed, examining the entirety of the population (N=40) through total sampling. Questionnaires were used to gather data, and SPSS version 25 was used for the purpose. The analysis employed multiple linear regression to investigate both the independent and combined influence of the predictor variables. The findings confirmed that employee performance was positively and significantly affected by transactional leadership. Employee performance has also been established to be positively and significantly affected by motivation. Employee performance was positively and significantly influenced by career development as well. These three causes all positively and significantly enhanced worker productivity at PT Erajaya Medan concurrently.